CRITICAL MULTILITERATION MODEL BASED ON APPROACH PROJECT BASED LEARNING IN DEVELOPING SKILLS THINKING METACOGNITION OF BASIC SCHOOL STUDENTS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The problem in this study is the low multiliteration ability of students, and the low development orientation of students' thinking skills in learning, especially metacognition thinking skills which is one of 21st century thinking skills. This is caused by several factors, one of the main factors is learning that is still oriented to the achievement of partial-textual knowledge and not to an integrative-contextual understanding of the knowledge learned. Therefore, there needs to be an effort that can be used as a solution to solve these problems through effective and up-to-date effective models that are oriented towards efforts to improve students' metacognition thinking skills, one of which is through the application of a critical militarized model based on aapproach project based learning. The critical multiliteration model is a learning model that is developed based on awareness and recognition of the diversity and complexity of the perspective of student culture and the diversity of learning styles it has. In addition, a critical multiliteration model is a model oriented towards efforts to build students' thinking skills through a multicontext, multicultural, and multimedia approach. In this context, a critical multiliteration model is developed specifically with a project-based approach as a dynamic learning approach, where students actively explore problems in the real world, provide challenges, and gain deeper knowledge. This is based on the purpose of developing a model that is oriented towards the development of metacognition thinking skills.